Jogos pedagógicos e aula de campo : uma proposta de sequência didática para o ensino dos conteúdos físico-naturais em geografia - Feltrin, Laura Maria Ortiz (2021)
The object of study of this dissertation is the teaching and learning of physical-natural content, with an emphasis on relief, in the subject of Geography in Basic Education. Studying the physical-natural contents, in particular the relief of the Parque Cuiabá-Chapada dos Guimarães Road, is the main objective of the work, considering the great geomorphological potential to work on such contents. It was also intended to provide means for students to understand the physical-natural content, which is studied in general, in textbooks, however, taking into account what is close to them. In addition, we thought of bringing students closer to the general and regional relief of Mato Grosso, offering didactic means to make the contents more attractive and easier for students to understand. To carry out the research, from the qualitative approach, the methodological procedures were chosen, such as: bibliographic survey and study, definition by the participant research technique from the development of a didactic sequence, we also conducted an interview, elaboration and application of a questionnaire , a pedagogical game, expository class, field class, and postfield. The results of this study indicate that understanding the concepts of relief, landscape and the development of some skills such as observing, identifying, comparing, researching and elaborating is essential for students. It is considered that, at the end of the activities, the view of the students in relation to society and nature in the space in which they live was expanded, considering the local and global scales. In this way, the renewal of teaching with the use of constructivist methodologies to instigate the student's learning process, with teachers committed to education, offering the opportunity for the construction of knowledge to occur through the subject, contributes to the formation of critical citizens and responsible for social relations and nature.